Sejarah Pelestarian dan Penyebaran Informasi: Menuju Masyarakat Informasi - Hasanah, Nuning; Suharto, Toto (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
The article aims to describe the information from a historical perspective. Knowledge of the history of information becomes important, considering that society is dynamic, transforms and shifts from an agricultural based-society to an industrial based, and recent becomes the information society today. Documentation technique used to collect data related to information preservation and information dissemination historically. This article uses historical analysis to explain the development of information, especially in its preservation and dissemination. This article found that the preservation of information has taken a long time, i.e. ever since humans as